Economic Interests of Saudi Arabia in Response to Uyghurs Human Rights Violation in XinJiang (2017-2019) - Andini Luthfiayu Intaningrum; Witri Elvianti (Intermestic: Journal of International Studies, 2021)
This study explains Uyghurs human rights violation in Xinjiang, where Saudi Arabia as world Islamic country has responded in passive way by not doing bold actions to defend the fellow Uyghurs muslims. In the meantime, the relationship between Saudi Arabia and China have become stronger as these countries become dependent towards each other, specifically with its economic cooperation especially under Belt and Road Initiatives. With the qualitative method, there is a high possibility that China utilizes passive response from Saudi Arabia as Saudi Arabia signed a joint-statement to appreciate China’s action on the issue against Uyghurs Muslims. This will lead to the Saudi Arabia’s economic interests as the reason behind its passive action in facing the human rights issue in Xinjiang as as Saudi Arabia is trying to maintain its normality with China for the sake of its bilateral relationship.